Chapter La CES e la politica europea della CGIL - Cerfeda, Walter (Studi e saggi, 2023)
The essay focuses on the role of trade union in the European integration, the strengthening of the European Trade Union Confederation, the European social dialogue and the relationship with the the President of the European Commission Delors. In particular, the essay illustrates Trentin's commitment to the recognition of a more straightforward negotiating role of the social partners. This was reached in 1991 when Ces, Unice and Ceep claimed from Delors' Commission the possibility of mandatory consultation in order to be able to negotiate directly afterwards, on all social issues on which the Commission intended to legislate. A diplomacy labor effort that later led to the establishment in 1992 of the European Social Dialogue Committee.